2018
DOI: 10.1530/ec-18-0384
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and combined oral contraceptives: a randomised, placebo-controlled trial

Abstract: ObjectiveThe effect of combined oral contraceptives (COCs) on female sexuality has long been a matter of discussion, but placebo-controlled studies are lacking. Thus, the aim of the present study was to investigate if an oestradiol-containing COC influences sexual function.DesignInvestigator-initiated, randomised, double-blinded, placebo-controlled clinical trial where 202 healthy women were randomised to a combined oral contraceptive (1.5 mg oestradiol and 2.5 mg nomegestrol acetate) or placebo for three trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…The existing literature is conflicting and mainly based on observational studies and a few randomised clinical trials focussing on the question of causality, comparisons between different oral contraceptives and reproductive hormone level changes [4][5][6]. One randomised study found no causality [7], another reported a small but clinically nonsignificant negative effect of combined oral contraceptives on sexual desire and lubrication [6]. Despite these uncertainties, many women may attribute impaired sexual function to their hormonal contraceptives, leading to difficulties finding a suitable method [8].…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature is conflicting and mainly based on observational studies and a few randomised clinical trials focussing on the question of causality, comparisons between different oral contraceptives and reproductive hormone level changes [4][5][6]. One randomised study found no causality [7], another reported a small but clinically nonsignificant negative effect of combined oral contraceptives on sexual desire and lubrication [6]. Despite these uncertainties, many women may attribute impaired sexual function to their hormonal contraceptives, leading to difficulties finding a suitable method [8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding modulating effects of hormonal status, sex hormone related differences have been observed in various emotional processes ( Montoya and Bos, 2017 ; Lundin et al, 2018 ; Lewis et al, 2019 ), including empathy components such as emotion recognition and affective responsiveness ( Derntl et al, 2013 ). In line with former studies ( Derntl et al, 2013 ; Radke and Derntl, 2016 ), hormonal status was associated to differences in the affective component of empathy.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to hormonal status, evidence is accumulating that female sex hormones like estradiol and progesterone (i.e., endogenous as well as synthetic) affect a variety of socio-emotional processes such as mood, fear processing, and sexual desire as well as arousal ( Montoya and Bos, 2017 ; Lundin et al, 2018 ; Lewis et al, 2019 ). It has been suggested that menstrual cycle dependent as well as OC-induced changes in mental states and behavior may be explained by a differential binding of endogenous (i.e., due to changing concentrations) as well as synthetic sex steroids (i.e., due to slightly different binding properties) to receptor sites of brain regions involved in socio-emotional processing (e.g., limbic areas and frontal cortex; Toffoletto et al, 2014 ; Barth et al, 2015 ; Louw-du Toit et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was initially validated in post-menopausal women but has shown reliability and validity in university women as well [15]. The Swedish version has been used in studies on oral anticontraceptive [16] and polycystic ovarian syndrome [17]. The original MFSQ contains 19 items, but several studies have used shorter versions, in which the number of items varies from nine to 17.…”
Section: Methodsmentioning
confidence: 99%